17β-Estradiol Treatment Improves Acetylcholine-Induced Relaxation of Mesenteric Arteries in Ovariectomized UC Davis Type 2 Diabetes Mellitus Rats in Prediabetic State - Razan, Md Rahatullah; Akther, Farjana; Islam, Rifat A.; Graham, James L.; Stanhope, Kimber L.; Havel, Peter J.; Rahimian, Roshanak (Frontiers in Physiology, 2022)
We recently reported sex differences in mesenteric artery (MA) function of the UC Davis type-2 diabetes mellitus (UCD-T2DM) rats as early as the prediabetic state. We reported that MA from prediabetic male rats exhibited a greater impairment compared to that in prediabetic females. However, when females became diabetic, they exhibited a greater vascular dysfunction than males. Thus, the aim of this study was to investigate whether the female sex hormone, estrogen preserves MA vasorelaxation in UCD-T2DM female rats at an early prediabetic state. Age-matched female Sprague Dawley and prediabetic (PD) UCD-T2DM rats were ovariectomized (OVX) and subcutaneously implanted with either placebo or 17β-estradiol (E2, 1.5 mg) pellets for 45 days. We assessed the contribution of endothelium-derived relaxing factors (EDRF) to acetylcholine (ACh)-induced vasorelaxation, using pharmacological inhibitors. Responses to sodium nitroprusside (SNP) and phenylephrine (PE) were also measured. Additionally, metabolic parameters and expression of some targets associated with vascular and insulin signaling were determined. We demonstrated that the responses to ACh and SNP were severely impaired in the prediabetic state (PD OVX) rats, while E2 treatment restored vasorelaxation in the PD OVX+E2. Moreover, the responses to PE was significantly enhanced in MA of PD OVX groups, regardless of placebo or E2 treatment. Overall, our data suggest that 1) the impairment of ACh responses in PD OVX rats may, in part, result from the elevated contractile responses to PE, loss of contribution of endothelium-dependent hyperpolarization (EDH) to vasorelaxation, and a decreased sensitivity of MA to nitric oxide (NO), and 2) the basis for the protective effects of E2 may be partly attributed to the elevation of the NO contribution to vasorelaxation and its interaction with MA as well as potential improvement of insulin signaling. Here, we provide the first evidence of the role of E2 in protecting MA from early vascular dysfunction in prediabetic female rats.